Moisture migration during a tempering time after the heat treatment step in yerba maté processing - Lovera, Nancy Noelia (2011)
The aim of this research was to study the effect of applying a tempering time to the branches of yerba maté after the heat treatment stage (or sapecado). Assays were carried out in three industrial producers of Misiones Argentina. Branches were obtained from the sapecador outlet and then, they were put in rest in order to form a bed. First, moisture content of leaves and twigs, separately, and then losses of mass of whole branches were measured. When the branches were put in rest in a bed during 30 min, 8.60 kg of water/100 kg of dry matter were transferred from the twigs to the leaves and 5.17 kg of water/ 100 kg of dry matter were lost by evaporation.